Anticonvulsant activity 2-((5-(3-(4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)-thio)-1-arylethanone - O. A. Bihdan (Zaporozhye State Medical University, 2019)
The aim of work is to study of the anticonvulsant activity of 2-((5-(3-,4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)thio)-1-aryletanones, the establishment of some laws between the structure of compounds and their activity. Materials and methods. The study of the anticonvulsant activity of 2-((5-(3-,4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)thio)-1-aryletanones was carried out according to the test of interaction with agents that excite the central nervous system. The experiments were performed on the intact white rats of the Vistar line, weight 160-190 g, five animals in each group. As convulsive models, corazole-induced convulsions were used, which was caused by subcutaneous administration of corazole at a dose of 100 mc/kg. Then the animals were placed in individual transparent flexiglaz cameras and watched them for one hour. Six indicators of convulsions were recorded: the latent period, the number of animals with generalized clonic or tonic-clonic convulsions in the group, the number of animals with tonic extension, mortality and life expectancy. Results. The resulting compounds exhibit high anticonvulsant activity. So, against the background of the introduction of 2-((5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-yl)thio)-1-(3-fluorophenylethanone), 2-((5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-yl)thio)-1-(4-fluorophenylethanone) and 2-((5-(4-fluorophenyl)-4-methyl-1,2,4-triazole-3-yl)thio)-1-(4-fluorophenylethanone), the latent period of the onset of convulsions under the influence of corazole increases by 57.1 %, 67.3 % and 28.6 %, respectively (P < 0.05 ), and the duration of convulsions is reduced by 33.4 %, 31.5 % and 38.9 %, respectively (P < 0.05), which indicates the neuroprotective and membrane stabilizing effect of the corresponding 2-((5-(3-4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)thio)-1-aryletanones. Comparison preparations of midocalm and phenobarbital increase the latent period of the onset of convulsive reactions by 51.0 % and 34.7 % at (P < 0.05), and the duration of convulsions decreased by 20.4 % and 14.9 % at (P < 0.05) respectively. Conclusions. The anticonvulsant activity of some 2-((5-(3-,4-fluorophenyl)-4-R2-1,2,4-triazole-3-yl)thio)-1-aryletanones was studied for the first time on a model of corazole convulsions. Three active compounds are 2-((5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-yl)thio)-1-(3-fluorophenylethanone), 2-((5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-yl)thio)-1-(4-fluorophenylethanone) and 2-((5-(4-fluorophenyl)-4-methyl-1,2,4-triazole-3-yl)thio)-1-(4-fluorophenylethanone). In some cases, regularities were revealed between the structure of molecules and their activity.